The Importance of People's Understanding of the Liturgy of the Catholic Church in the Border Areas of Indonesia and the State of Timor Leste - Yohana Aek Klau (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the importance of people's understanding of the liturgy of the Catholic Church in the border area of Indonesia and Timor Leste. The research was carried out through a descriptive qualitative approach with interviews, observations, and documentation methods of parish priests, catechists, liturgical officers, and local faithful. The research process was carried out during a scheduled pastoral observation period in the border parish environment. The results of the study show that the level of understanding of the meaning and order of liturgical celebrations still varies, influenced by the background of faith education, liturgical guidance, and the local cultural context. These findings affirm the importance of contextually strengthening liturgical catechesis in order to increase the active participation of the faithful in the liturgical life of the Church in the border areas.